2014
DOI: 10.1371/journal.pone.0100199
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Dimension of EEG Activity Senses Neuronal Impairment in Acute Stroke

Abstract: The brain is a self-organizing system which displays self-similarities at different spatial and temporal scales. Thus, the complexity of its dynamics, associated to efficient processing and functional advantages, is expected to be captured by a measure of its scale-free (fractal) properties. Under the hypothesis that the fractal dimension (FD) of the electroencephalographic signal (EEG) is optimally sensitive to the neuronal dysfunction secondary to a brain lesion, we tested the FD’s ability in assessing two k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(96 citation statements)
references
References 83 publications
5
88
2
1
Order By: Relevance
“…The time-variability properties of the EEG signals could instead have an organized complex structure, reflecting non-linear characteristics of the system that are deeply linked to the underlying organ functioning [23]. Indeed, fractal nature of a signal has often been used to quantify the topological and functional complexity of processes generating that signal [23].…”
Section: Discussionmentioning
confidence: 99%
“…The time-variability properties of the EEG signals could instead have an organized complex structure, reflecting non-linear characteristics of the system that are deeply linked to the underlying organ functioning [23]. Indeed, fractal nature of a signal has often been used to quantify the topological and functional complexity of processes generating that signal [23].…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in complexity may be an indication of neural activity moving away from a fractal dynamic. A study based on the complexity of EEG activity in stroke patients showed a decrease in fractal dimension for patients with lesions in the left or right hemispheres of the brain during the acute phase of stroke [140]. The lower fractal dimension was more noticeable in the affected area.…”
Section: Fractal Dynamics In Physiological Systemsmentioning
confidence: 99%
“…Several studies have found a decreased or abnormal complexity in the EEG activity of other various mental ailments including depression [138] [139], brain lesions due to stroke [140], schizophrenia [138] [141], and Alzheimer's disease [142] [143]. A reduction in complexity may be an indication of neural activity moving away from a fractal dynamic.…”
Section: Fractal Dynamics In Physiological Systemsmentioning
confidence: 99%
“…During years different works have been reported in literatures which focused on analysis of neurophysiological time series using fractal theories [1][2][3][4][5][6][7][8][9][10]. In a recent work on prediction of epileptic seizure onset we proposed a new methodology which is based on studying the EEG signals using two measures, the Hurst exponent and fractal dimension.…”
Section: Hamidreza Namazimentioning
confidence: 99%